Function: Series addition implementation

조회 수: 1 (최근 30일)
Kamilu Sanusi
Kamilu Sanusi 2023년 1월 29일
댓글: Walter Roberson 2023년 2월 2일
Hello
I am trying to solve an equation of which i need to be using the new values of V and delta as an update in equations (1).The closed equation (1) when expanded will be in the form of equation (2) for i = 2 and j is between 1 -5.
% P(i) = sum(j=1->n) |Vi||Vj|(Gij * cos(delta_i - delta_j) + Bij * sin(delta_i - delta_j) EQUATION (1) % The formula for calculating the P
Implementation of P(2) for example:
P(2) = P(2) + V(2)*V(1)*(G(2,1)*cos(delta(2)-delta(1)) + B(2,1)*sin(delta(2)-delta(1))) + V(2)*V(2)*(G(2,2)*cos(delta(2)-delta(2)) + B(2,2)*sin(delta(2)-delta(2))) + V(2)*V(3)*(G(2,3)*cos(delta(2)-delta(3)) + B(2,3)*sin(delta(2)-delta(3))) + V(2)*V(4)*(G(2,4)*cos(delta(2)-delta(4)) + B(2,4)*sin(delta(2)-delta(4))) + V(2)*V(5)*(G(2,5)*cos(delta(2)-delta(5)) + B(2,5)*sin(delta(2)-delta(5))) EQUATION (2)
Please is the below program good enough to represent the expansion of P(2) in equation (2) as an example ?
% Program
P = zeros(nbus,1);
Q = zeros(nbus,1);
V = zeros(nbus,1);
% B and G are constants
% Computing P
% nbus = 5
for i = 1:nbus
for j = 1:nbus
if type(i) == 2 % Computing Pi & Qi for Droop bus
P(i) = V(i)*V(j)*(G(i,j)*cos(delta(i)-delta(j)) + ...
B(i,j)*sin(delta(i)-delta(j)))+ PO(i)-PL(i);
Q(i) = V(i)*V(j)*(G(i,j)*sin(delta(i)-delta(j)) - ...
B(i,j)*cos(delta(i)-delta(j)))+ QO(i)-QL(i);
end
end
end
  댓글 수: 5
Dyuman Joshi
Dyuman Joshi 2023년 1월 31일
편집: Dyuman Joshi 2023년 1월 31일
Okay. But still have not answered my other queries.
The equation in the link do not contain PO, PL, QO and QL, where as your code does.
Walter Roberson
Walter Roberson 2023년 2월 2일
for i = 1:nbus
for j = 1:nbus
if type(i) == 2 % Computing Pi & Qi for Droop bus
That is inefficient. type(i) does not change according to changes in j, so you should be testing type(i) outside the for j loop, only executing the for j loop if type(i) == 2
P(i) = V(i)*V(j)*(G(i,j)*cos(delta(i)-delta(j)) + ...
B(i,j)*sin(delta(i)-delta(j)))+ PO(i)-PL(i);
Q(i) = V(i)*V(j)*(G(i,j)*sin(delta(i)-delta(j)) - ...
B(i,j)*cos(delta(i)-delta(j)))+ QO(i)-QL(i);
P(i) does not depend upon P(i) or Q(i) so at each different j you completely overwrite P(i) and Q(i) and the final result will be the same as if you had only done the final j=nbus .

댓글을 달려면 로그인하십시오.

답변 (0개)

카테고리

Help CenterFile Exchange에서 Calculus에 대해 자세히 알아보기

제품


릴리스

R2021b

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by